Upstream, downstream - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Land-water linkages in rural watersheds FAO (includes a CD ROM), 2002. 88 pp. ISBN 9251047650 US$ 14 Euro 13.60